Energy Conversion-Based Nanotherapy for Rheumatoid Arthritis Treatment - Wang, Pingping; Li, Ao; Yu, Luodan; Chen, Yu; Xu, Di (Frontiers in Bioengineering and Biotechnology, 2020)
Rheumatoid arthritis (RA) is characterized by synovial hyperplasia and cartilage/bone destruction, which results in a high disability rate on human health and a huge burden on social economy. At present, traditional therapies based on drug therapy still cannot cure RA, in accompany with the potential serious side effects. Based on the development of nanobiotechnology and nanomedicine, energy conversion-based nanotherapy has demonstrated distinctive potential and performance in RA treatment. This strategy employs specific nanoparticles with intrinsic physiochemical properties to target lesions with the following activation by diverse external stimuli such as light, ultrasound, microwave, and radiation. These nanoagents subsequently produce therapeutic effects or release therapeutic factors to promote necrotic apoptosis of RA inflammatory cells, reduce the concentration of related inflammatory factors, relieve the symptoms of RA, which are expected to ultimately improve the life quality of RA patients. This review highlights and discusses the versatile biomedical applications of energy conversion-based nanotherapy in efficient RA treatment, in together with the deep clarification of the facing challenges and further prospects on the final clinical translations of these energy conversion-based nanotherapies against RA.